(untitled) - Willems, Mo; Keller, Laurie (New York, 2016)
"Walt is not the tallest or the curliest or the pointiest or even the crunchiest. A confounded blade of grass searches for his 'est' in this ... story about growing up"--
Keywords: JUVENILE FICTION / Concepts / General; Grasses; Humorous Stories; JUVENILE FICTION / Humorous Stories; Fiction; Juvenile fiction; Fiction; Growth; Juvenile fiction; JUVENILE FICTION / Social Issues / Values & Virtues; Growth; Grasses